Education Is it an Empowering factor against Domestic Violence in India? - Arya, Manju (JOURNAL OF INDIAN EDUCATION, 2020)
This work examines the domestic violence in multi-dimensional perspective to demonstrate the relationship between education and domestic violence. The previous research argued that improvements in women’s education would raise their awareness and thereby reduce violence against them. The findings of the researchers are in support that the main cause of domestic violence is lack of education. Taking this as a hypothesis the work focused on the comparative analysis of domestic violence in Rajasthan and Kerala. Rajasthan is considered as the state with lowest female literacy rate whereas Kerala is considered as the state with highest female literacy rate. The analysis of the NFHS data showed the result that both lack of education and rising levels of education among women has negligible effect on protection of women from violence against them. In fact, the temporal analysis showed the increasing trend in the percentage of women in Kerala who have completed ten or more years of education are more vulnerable to all forms of violence than the women in Rajasthan.